Maximize the value of m + n where m and n are positive integers satisfying:
m 2 + 2 ⋅ 3 n = m ( 2 n + 1 − 1 )
Inspired by an IMO problem, but pretty much nothing like it, so Daniel Liu doesn't have to worry. :D
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Excellent! First solver and AMAZING solution.
Log in to reply
My pleasure, I enjoyed solving it. So thanks for sharing.
Also, would you mind making it more clear that the solution is ( 5 4 , 5 ) to the reader, because it's kind of buried among a bunch of confusing-looking L A T E X . Thanks! :D
Log in to reply
True, done :)
Log in to reply
Your solution assumes m < 1 0 0 0 :(
Log in to reply
@Daniel Liu – Daniel you are so sad aren't you... D:
@Daniel Liu – Yeah, I know, sorry about that. I mentioned how to do it in general in the remark by analyzing the orbits of 2 in mod 3 a rings, but that's probably an overkill. I guess it should be possible to show that k and n must be small by some standard inequalities involving the equation. Or, by a different solution altogether. So looking forward to yours ;)
Log in to reply
@Marek Bernat – Unfortunately, I didn't really solve it all that legitimately. I didn't prove that my solution was the maximum.
Actually if one knows all the of this problem, (aldready available,question is trivialws
Problem Loading...
Note Loading...
Set Loading...
First rewrite the equation as m ( 2 n + 1 − 1 − m ) = 2 ⋅ 3 n . Suppose first that m is odd and therefore that m = 3 k for some k . We then get 2 n + 1 − 1 − 3 k = 2 ⋅ 3 n − k . On the other hand, if m were even then m = 2 ⋅ 3 l and so 2 n + 1 − 1 − 2 ⋅ 3 l = 3 n − l . We observe that this is the same equation as for m odd after letting l = n − k . Rewriting this a bit, we have 2 n + 1 − 1 = 3 a ( 2 ⋅ 3 b + 3 c ) , where 3 a is greatest common denominator of 3 k and 3 n − k and b c = 0 .
Now fix a and let us try to solve the equation 2 n + 1 ≡ 1 ( m o d 3 a ) . First observe what happens for small values of a . If a = 1 then it's enough that n + 1 be even. When a = 2 , we get the sequence 2 , 4 , 8 ≡ − 1 , − 2 , − 4 , 1 , i.e. n + 1 must be a multiple of 6 . When a = 3 , the sequence is 2 , 4 , 8 , 1 6 , 3 2 ≡ 5 , 1 0 , 2 0 , 4 0 ≡ 1 3 , 2 6 ≡ − 1 , … , − 2 0 , − 1 3 , 1 having 18 terms in total, so that n + 1 must be divisible by 18. In general the length of the sequence divides 2 ⋅ 3 a − 1 since that is the number of elements of Z / ( 3 a ) Z which are not divisible by 3 . I'm not sure how n depends a in general (and we will not be needing that result in what follows) but my guess is that it will be quite non-trivial and probably grow exponentially (i.e. n ∼ 3 a )
We will now show that k is large whenever n is. From the main equation we have 2 n ≥ 3 n − k and after taking logarithm n ≥ ( n − k ) lo g 2 3 , so that k ≥ n ( lo g 2 3 − 1 ) / lo g 2 3 .
Realizing that m < 1 0 0 0 we must have k ≤ 6 and therefore from the above n ≤ 2 0 , for which our analysis above implies a ≤ 3 . Let us now investigate the cases.
When a = 3 we must have n = 1 7 . Therefore 2 n + 1 − 1 = 2 1 8 − 1 = 3 3 ⋅ 9 7 0 9 . Because 9 7 0 9 has remainder 1 after dividing by 3 we need that ( 9 7 0 9 − 1 ) / 2 be a power of 3 which is not the case.
When a = 2 we have n = 5 or n = 1 1 . We get 2 6 − 1 = 6 3 = 3 2 ⋅ 7 and 7 = 2 ⋅ 3 1 + 1 , so this one works with k = 3 and we obtain m = 2 ⋅ 3 3 = 5 4 so that n + m = 5 9 . For n = 1 1 we get 2 1 2 − 1 = 4 0 9 5 = 9 ⋅ 4 5 5 . 4 5 5 has remainder 2 after dividing by 3, so that b = 0 and 4 5 5 − 2 would need to be a power of 3 . This is again not the case.
For a = 1 one can either check the cases by hand or simply realize that we can't get n better than 2 0 or m better than 2 ⋅ 3 1 = 6 , so this would not beat our best result. So the final answer is 5 9 obtained from n = 5 , m = 5 4 in the case a = 2 above.
Final remark: if we knew that the dependence of n on a was exponential, that alone would be enough to show that both n and k must be small (without the need to cheat by using that the result must be less than 1000).